Regulation of morphogen pathways by a Drosophila chondroitin sulfate proteoglycan Windpipe. - Koh, W.S.; Knudsen, C.; Izumikawa, T.; Nakato, E.; Grandt, K.; Kinoshita-Toyoda, A.; Toyoda, H.; Nakato, H. (Journal of Cell Science, 2023)
Morphogens provide quantitative and robust signaling systems to achieve stereotypic patterning and morphogenesis. Heparan sulfate (HS) proteoglycans (HSPGs) are key components of such regulatory feedback networks. In Drosophila, HSPGs serve as co-receptors for a number of morphogens, including Hedgehog (Hh), Wingless (Wg), Decapentaplegic (Dpp) and Unpaired (Upd, or Upd1). Recently, Windpipe (Wdp), a chondroitin sulfate (CS) proteoglycan (CSPG), was found to negatively regulate Upd and Hh signaling. However, the roles of Wdp, and CSPGs in general, in morphogen signaling networks are poorly understood. We found that Wdp is a major CSPG with 4-O-sulfated CS in Drosophila. Overexpression of wdp modulates Dpp and Wg signaling, showing that it is a general regulator of HS-dependent pathways. Although wdp mutant phenotypes are mild in the presence of morphogen signaling buffering systems, this mutant in the absence of Sulf1 or Dally, molecular hubs of the feedback networks, produces high levels of synthetic lethality and various severe morphological phenotypes. Our study indicates a close functional relationship between HS and CS, and identifies the CSPG Wdp as a novel component in morphogen feedback pathways.